2021
DOI: 10.3991/ijoe.v17i09.24791
|View full text |Cite
|
Sign up to set email alerts
|

The Mental Health Impact of COVID-19 Pandemic on Health Care Workers and Coping Strategies: A Systematic Literature Review

Abstract: <strong>Background</strong>: In December 2019, the COVID-19 outbreak originated in Wuhan, China. Since then, this virus has spread at a very rapid rate affecting many countries. The World Health Organization (WHO) subsequently declared a global pandemic, and a range of precautions have been implemented to reduce the spread of the virus. Some of these precautions included social distancing, self-isolation, and quarantine of those who have contracted or potentially contracted COVID-19. Healthcare wor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 48 publications
(130 reference statements)
0
6
0
Order By: Relevance
“… 11 Another study reported poor or worse well-being from nurses caring for COVID-19 patients compared to co‐workers. 12 The high levels of anxiety and depression nurses experienced during the pandemic have also been found to be associated with low general health and high insomnia. 13 Furthermore, many studies have shown the adverse effects of the pandemic on healthcare workers, such as depression and anxiety and found higher rates among nurses than other health workers during the pandemic.…”
Section: Introductionmentioning
confidence: 99%
“… 11 Another study reported poor or worse well-being from nurses caring for COVID-19 patients compared to co‐workers. 12 The high levels of anxiety and depression nurses experienced during the pandemic have also been found to be associated with low general health and high insomnia. 13 Furthermore, many studies have shown the adverse effects of the pandemic on healthcare workers, such as depression and anxiety and found higher rates among nurses than other health workers during the pandemic.…”
Section: Introductionmentioning
confidence: 99%
“…• Emotional Exhaustion (EE) composed of 9 items (1,2,3,6,8,13,14,16,20) and (result between 0 and 54). • Depersonalization (DP) composed of 5 items (5,10,11,15,22) and (result between 0 and 30).…”
Section: Methodsmentioning
confidence: 99%
“…Indeed, to protect the psychological health [8] of these resources, it is necessary to produce a diagnostic tool for burnout valid for the cultural context of teachers.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, the infectious disease COVID-19, caused by the new SARS-CoV-2 coronavirus was first detected in Wuhan, China. Since then, the virus has affected global society, including Peru, spreading at an accelerated rate, having a catastrophic effect worldwide [1], [2]. The international community and local governments were forced to implement restrictions and social distancing as measures to minimize the spread of this new coronavirus [3], [4]; as a consequence of these measures implemented, economic and social activity was affected causing an increase in anxiety, stress and depression in people around the world, as these are effects of emotional disorders that specially affect mental health [5].…”
Section: Introductionmentioning
confidence: 99%